(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
The study was carried out to analyse the profitability of women in cassava enterprises in Ogbomoso agricultural zone of Oyo- State, Nigeria. The specific objectives of the study were meant to describe the socio-economic characteristics of women, evaluate the costs and returns for cassava tubers and cassava products, estimate the profitability ratio and identify the problems encountered by women in cassava production and processing. A multistage sampling method was used to select samples from Oriire, Ogo-Oluwa and Surulere Local Government Areas in Ogbomoso Agricultural Zone and the sample size was one hundred and sixty respondents. Structured questionnaire were used to elicit information from the selected respondents and it was structured in line with the objectives of the study. Data were analysed using descriptive statistics, budgetary and profitability ratio techniques. Average total cost of producing cassava tubers and processing cassava tubers were N57,697.50k per hectare and N599,929.70k per month respectively. Average total cost for combining production and processing of cassava tubers was N1,500, N650.00k per annum. The net returns for women cassava producers and those women that combined cassava production and processing were N221,052.00k and N7,289,950.00k per annum respectively. The benefit cost ratio (BCR) for the women cassava producers, processors and those women that combined production and processing were 4.83,1.08 and 5.86 respectively. These showed that the enterprises were profitable. The combination of cassava production and processing by women was found to be most profitable.